Vaccine hesitancy in context of COVID-19 in East Africa: systematic review and meta-analysis - Melsew Setegn Alie; Gossa Fetene Abebe; Yilkal Negesse; Amanuel Adugna; Desalegn Girma (BMC, 2024)
Abstract Background The outbreak of the SARS-CoV-2 pandemic has had a significant impact on human lives, and the development of effective vaccines has been a promising solution to bring an end to the pandemic. However, the success of a vaccination program heavily relies on a significant portion of the population being vaccinated. Recent studies have indicated a rise in vaccine hesitancy over time and inconsistent factors affecting it. This study aimed to synthesis of the pooled prevalence of COVID-19 vaccine hesitancy and associated factors among various communities in East Africa. Methods The review encompassed relevant descriptive and observational studies conducted between January 1, 2020, and December 26, 2023. We browsed various databases, including PubMed, Google Scholar, Scopus, African online Journal, cross-references, and Web of Science. After extracted and exported to R the data analysis was performed using R version 4.2. Meta-package were used to estimate the pooled prevalence and factors of vaccine hesitancy. Publication bias was assessed through funnel plots, Egger's test, and trim-and-fill methods. Results After carefully screening an initial pool of 53,984 studies, a total of 79 studies were included in this systematic review and meta-analysis. The overall pooled prevalence of vaccine hesitancy was 40.40% (95% CI: 35.89%; 45.47%, I2: 99.5%). Identified factors influencing vaccine hesitance were female sex, under 40 years old, inadequate prevention practices, relying on web/internet as a source of information, having a negative attitude towards the vaccine, uncertainty about vaccine safety, fear of adverse effects, uncertainty about contracting COVID-19, and belief in conspiracy myths. Conclusions Approximately four out of ten individuals in this region express hesitancy towards vaccination. A tailored approach that considers the socio-demographic context could significantly reduce this hesitancy. To achieve high vaccination coverage, a comprehensive strategy is essential, necessitating substantial social, scientific, and health efforts. The success of vaccination campaigns within this population relies on the widespread and consistent implementation of effective interventions. Registration Registered in PROSPERO with ID: CRD42024501415.